2009
DOI: 10.1007/s00414-009-0372-5
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a minimum postmortem interval of human remains in an advanced state of skeletonization using the growth rate of bryophytes and plant roots

Abstract: This paper illustrates the usefulness and efficiency of botanical evidence in establishing a minimum postmortem interval (PMI). The case under analysis refers to the remains of an adult male in an advanced state of skeletonization recovered from a wooded area in northern Portugal. The skeleton showed several taphonomical changes, which included the presence of green algae, bryophytes, and growing shrub roots in, around, and through the remains. By determining the age of both the bryophytes and shrub roots, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 21 publications
0
15
0
2
Order By: Relevance
“…These cases occurred between October 1991 to January 1995 and all exhibited mild to moderate sun bleaching from exposure on land as well as a dull green, dark brown, or black algal staining. Cardoso et al (2010) presented a case study in which a skeletonized set of remains was recovered in a wooded environment, disturbed by various plant species, and displayed staining from contact with soil and sun exposure. The remains displayed growth of algae and moss on the bone surfaces, which begin to infiltrate the remains once soft tissue had completed decomposition (Cardoso et al 2010).…”
Section: Plant/wood Stainingmentioning
confidence: 99%
See 2 more Smart Citations
“…These cases occurred between October 1991 to January 1995 and all exhibited mild to moderate sun bleaching from exposure on land as well as a dull green, dark brown, or black algal staining. Cardoso et al (2010) presented a case study in which a skeletonized set of remains was recovered in a wooded environment, disturbed by various plant species, and displayed staining from contact with soil and sun exposure. The remains displayed growth of algae and moss on the bone surfaces, which begin to infiltrate the remains once soft tissue had completed decomposition (Cardoso et al 2010).…”
Section: Plant/wood Stainingmentioning
confidence: 99%
“…Cardoso et al (2010) presented a case study in which a skeletonized set of remains was recovered in a wooded environment, disturbed by various plant species, and displayed staining from contact with soil and sun exposure. The remains displayed growth of algae and moss on the bone surfaces, which begin to infiltrate the remains once soft tissue had completed decomposition (Cardoso et al 2010). The authors suggested that botanical evidence found on the remains can aid in the estimation of PMI through the calculation of the growth period of the particular plant.…”
Section: Plant/wood Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Bitkilerden yola çıkılarak yapılacak tahmin, iskeletleşme süre-cinde de kayda değer sonuçlar verebilmektedir. Ancak ileri dönemlerde bu yöntemler de yetersiz kalmaktadır (1,12).…”
Section: öLüm Zamanı Tahmininde Başvurulan Morfolojik Yöntemlerunclassified
“…Cesetlerin dekompozisyon seviyesi ilerlediği veya komple iskeletleşme gerçekleştiği zaman, dekompozisyon oranındaki çeşitlilik ve postmortem deği-şiklikler ölüm zamanı tahminini komplike hale getirmektedir. Bu aşamadaki böceklerin aktiviteleri ve yaşamsal döngüsü gibi bazı bulgular ölümün üzerinden uzun süre geçmeye başladıkça kullanışlılığını kaybetmektedir (1).…”
Section: Introductionunclassified